Effects Of Time-Dependent Deformation On The Strength Of Masonry - Said, Syamsuhaili (2010)
Influence of unit type on the deformation of masonry structure is very important owing to different type of fired-clay brick available in the local market. Most of research published on fired-clay brick, especially on time-dependent movement, were from other countries, mostly in the United Kingdom and rarely be found in Malaysia. Therefore, it is necessary to conduct the study due to a lack of information and misleading perception that local bricks are of low quality and are becoming unpopular building materials as compared to concrete.